Collapse of an Online Social Network: Who Started the Avalanche? - Lorincz, Laszlo; Gyor, Anna Fruzsina; Koltai, Julia; Karoly, Takacs (AoIR Selected Papers of Internet Research, 2016)
iWiW was a Hungarian online social network (OSN), founded in 2002. By 2008 two-third of the Hungarian internet-using population became its user, however, in the following years substitution of iWIW with Facebook increased, until 2014, when the closing down of the site was announced. The goal of our research is uncovering the sociological and economic mechanisms explaining the collapse of the iWiW. After significant cascading mechanism were found in the abandoning of the site, this study concentrates on the specification of users, who left the OSN first, and started these avalanches. Using the whole database of the iWiW network exported in 2013, we classified users to ‘early leavers’ (who left the site when more than 90% of their friends were active); and ‘non-early leavers’ (who left when more than 10% of their friends became inactive). Multivariate regression models reveal that lower degree is associated with higher probability of leaving the network early for the whole period. The positive effect of locally open networks is also visible: high local clustering coefficient increases the chance of leaving iWiW early. However, the effect of innovativeness can also be observed: those, who joined earlier than a typical member of their age group, also tended to leave earlier.